Siloed discourses: a year-long study of twitter engagement on the use of CRISPR in food and agriculture - Lauren Crossland-Marr; Alexandru Giurca; Maya Tsingos; Matthew A. Schnurr; Adrian Ely; Dominic Glover; Glenn Davis Stone; Klara Fischer (New Genetics and Society, 2023)
Gene editing technologies are emerging as powerful tools for agricultural development, spurring both hopes and concerns in society. To understand emerging discourses and coalitions around the role of CRISPR gene editing in food and agriculture we map the main actors and themes emerging from English-speaking Twitter networks over the course of one year (2021). Scientific actors are the most active and best networked in the debate. They promote a positive image of CRISPR gene editing and actively work to strengthen their network. A smaller but equally distinct group comprises civil society actors, who voice skepticism towards the technology and sometimes questions scientists’ claims, but without eliciting responses from the scientists. We conclude that emerging discourse coalitions forming around the topic of CRISPR in food and agriculture on Twitter are siloed, with limited interaction between contrasting perspectives.